DIGITAL TECHNOLOGIES AND EDUCATIONAL OPPORTUNITIES - Туленова Карима Жандаровна (Journals Park Publishing, 2024)
The article reveals the importance of digital technologies and their capabilities in education. The improvement of modern education is inextricably linked with the development of digital technologies, the introduction of which contributes to the modernization and development of education, improving the quality of training of future specialists, as well as to the convergence of education with science.
Keywords: digital technologies, science, education, modernization, technologies in education, digital culture, upbringing.